Increasing Waroung Sehat’s Brand Awareness by Creating USP-Based TikTok Catalogue and Contents - Ferren Janice Chen; Ivonne Muliawati Harsono (Institute of Research and Community Outreach - Petra Christian University, 2026)
Waroung Sehat is an online business selling imported herbal supplements to customers aged 30–70 who seek natural solutions for their illnesses. Despite having quality products and online presence on platforms like Shopee, the company struggles with low brand awareness, worsened by a banned TikTok account, as well as weak, outdated contents. To validate the problem, the writer distributed a questionnaire through Google Forms. The responses confirmed poor awareness, unclear product information, and low brand recognition. The proposed solutions for this issue are USP-based TikTok contents and catalogue. This project includes three major changes to its catalogue, video contents, and carousels optimized for TikTok’s algorithm and video shopping. This approach is effective because it matches TikTok’s content style, boosts visibility, and communicates clear product benefits. Moreover, it is also affordable and sustainable for the company’s limited resources. By applying this strategy, Waroung Sehat can rebuild its TikTok presence, attract attention, increase engagement and sales, and turn digital visibility into real business growth.